The effect of service quality and coach competency on the motivation and achievement of Riau basketball student-athletes - Ardiah Juita,; Tomoliyus,; Awan Hariono,; Syahriadi,; Endang Rini Sukamti,; Fauzi,; Abdul Alim,; Trisnar Adi Prabowo, (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to assess the correlation between each variable of service quality and coach competency and their impact on the achievement of basketball athletes, with motivation acting as a mediating variable in this relationship. This study is a correlational descriptive study using the Structural Equation Model (SEM) approach with the help of smart PLS. The study comprised a sample of 100 basketball student-athletes from Riau province. Data collection involved the use of questionnaires; however, to complement this quantitative approach, interviews with athletes are still considered necessary as a qualitative method. The results revealed that the coach's competency significantly relates to the achievement, with a p-value of 0.004, the competency of the coach to the motivation with a p value of 0.000, the motivation to the achievement (p < 0.000), the quality of service to the achievement of (p < 0.001), the quality of service to the motivation (p < 0.003), the competency of the coach to the achievement of the motivation (< 0.000), the quality of service to the achievement of the motivation (p < 0.007). The quality of service and competence of basketball coaches has a strong relationship with the achievements of basketball athletes. Motivation also plays an important role as a mediating variable, demonstrating that the quality of service and the competence of basketball coaches can significantly enhance the achievement of student basketball athletes through motivation. It is expected that the results of this study can be used as a reference to coaches, sports academics, official basketball clubs, and related parties in basketball to pay more attention to the quality of service, especially training sites and competent coaches.